Chemical compound isolated from antioxidant active extract of endophytic fungus Cladosporium tenuissimum in Swietenia mahagoni leaf stalks - Fadhillah Fadhillah; ELFITA; MUHARNI; HENI YOHANDINI; HARY WIDJAJANTI (Society for Indonesian Biodiversity, 2019)
Abstract. Fadhillah, Elfita, Muharni, Yohandini H, Widjajanti. 2019. Chemical compound isolated from antioxidant active extract of endophytic fungus Cladosporium tenuissimum in Swietenia mahagoni leaf stalks. Biodiversitas 20: 2645-2650. Swietenia mahagoni L. Jacq is a medicinal plant that widely used as an antimicrobial, anti-inflammatory, antimutagenic, anticancer, antitumor, and antidiabetic. Several bioactive compounds have been reported to be associated with this plant that supports its treatment activities. Flavonoid content of the S. mahagoni has antioxidant activity. Therefore the plant is widely used to treat degenerative diseases caused by free radical activity in the body. Scientists have proven that the medicinal plants have a symbiotic relationship with the number of microorganisms that can produce bioactive compounds. One of the symbiotic microorganisms is endophytic fungi believed to be associated with every plant on earth. In this paper, we report a secondary metabolite compound from endophytic fungi isolated from S. mahagoni. The endophytic fungi (DMG1-DMG4) were isolated from leaf stalks of S. mahagoni. Antioxidant activity of endophytic fungi extracts was tested by 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The chemical compound from the active extract was isolated by the chromatographic method, and the structure was elucidated by spectroscopic methods including UV, IR, NMR 1D (1H-NMR and 13C-NMR), NMR 2D (HMQC and HMBC). Antioxidant activity test showed the endophytic fungus (DMG3) has the highest activity. The chemical compound from DMG3 was identified as 5-hydroxy-2-oxo-2H-piran-4-yl) methyl acetate). The phylogenetic method used to molecular analysis of DMG3 confirmed the fungus as Cladosporium tenuissimum.